146k views
1 vote
If f(x) = 27 +3 and g(x) = x - 7, find (f - g)(x).

2 Answers

5 votes

Answer:

(f - g)(x) = 26x + 10

Explanation:

(f - g)(x) = f(x) - g(x)

We have f(x) = 27x + 3 and g(x) = x - 7. Substitute:

(f - g)(x) = (27x + 3) - (x - 7)

(f - g)(x) = 27x + 3 - x - (-7)

(f - g)(x) = 27x + 3 - x + 7 combine like terms

(f - g)(x) = (27x - x) + (3 + 7)

(f - g)(x) = 26x + 10

User Blancos
by
5.1k points
6 votes

Answer:

(f - g)(x) = 37 - x

Explanation:

(f - g)(x) = (27 +3) - (x - 7)

= 27 + 3 - x + 7

= 37 - x

User Harry Cutts
by
4.9k points